Respuesta :
3a^3-5b^3+xa^3+yb^3=1a^3+1b^3
3z-5v+xz+yv=z+v
3z+xz+yv-5v=1z+v
3z+xz=1z
3+x=1
x=-2
yv-5v=1v
y-5=1
y=6
(3a^3-5b^3)+ -2 a^3 +6 b^3=(a^3+b^3)
3z-5v+xz+yv=z+v
3z+xz+yv-5v=1z+v
3z+xz=1z
3+x=1
x=-2
yv-5v=1v
y-5=1
y=6
(3a^3-5b^3)+ -2 a^3 +6 b^3=(a^3+b^3)
3a^3-5b^3+xa^3+yb^3=1a^3+1b^3
replace a^3 with z
replace b^3 with v (to make it easier to see)
3z-5v+xz+yv=z+v
3z+xz+yv-5v=1z+v
the terms match them
3z+xz=1z
divide both sides by z
3+x=1
minus 3
x=-2
yv-5v=1v
dividie both sides by v
y-5=1
addd 5 to both sides
y=6
(3a^3-5b^3)+ -2 a^3 +6 b^3=(a^3+b^3)
replace a^3 with z
replace b^3 with v (to make it easier to see)
3z-5v+xz+yv=z+v
3z+xz+yv-5v=1z+v
the terms match them
3z+xz=1z
divide both sides by z
3+x=1
minus 3
x=-2
yv-5v=1v
dividie both sides by v
y-5=1
addd 5 to both sides
y=6
(3a^3-5b^3)+ -2 a^3 +6 b^3=(a^3+b^3)